Assessment of Plastic Energy Demand Spectra on Frame Systems - Anıl Dindar, A. Anil; Polat, Gökhan; Yalçın, Cem; Yüksel, Ebubekir; Özkaynak, Hasan; Büyüköztürk, Oral (Springer Science and Business Media Deutschland GmbH, 2021)
Determination of structural resistance to seismic loads is a complex problem. To overcome the complexity, simple but efficient methods have been developed for engineers. In that process for the sake of simplicity and practicality, certain assumptions are made in defining seismic demand. One of the them is energy dissipation by structural members during seismic actions. However, energy dissipation is directly related to damage occurrence and propagation in the member. Calculation of plastic energy to be dissipated by structural member requires definition of energy demand on the structural system. This study aims to assess plastic energy spectrum approach on frame type reinforced concrete structures. Plastic energy demand values on three frame systems representing low- to mid-rise buildings are obtained from plastic energy spectrum and also nonlinear time history analysis (NLTH). Plastic energy spectrum is taken from the previous study of the authors. Comprehensive NLTH analyses on selected frame systems are conducted on the pre-designed systems which consists of concentrated plastic hinges. Moment and rotation response time histories of the structural members are used in calculation of energy dissipation. Comparisons between spectra- and NLTH-based results are made on three systems. For low-rise system, both plastic energy dissipation values are found approximate whereas for mid-rise systems, plastic energy spectrum is found conservative. The numerical examples reveal that plastic energy spectrum is a robust concept for energy-based design methodologies. © 2021 Elsevier B.V., All rights reserved.
1st International Workshop on Energy-Based Seismic Engineering, IWEBSE 2021 -- Madrid -- 258499
Keywords: Damage; Energy dissipation; Nonlinear time-history analysis; Plastic energy demand spectrum; RC frame